2020
DOI: 10.3390/ijerph17010347
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Intervention Programs for Preventing Obesity and Promoting Physical Activity and Fitness: A Systematic Review

Abstract: With the significant decrease in physical activity rates, the importance of intervention programs in the schools, where children spend a significant part of the day, has become indisputable. The purpose of this review is to systematically examine the possibility of school-based interventions on promoting physical activity and physical fitness as well as preventing obesity. A systematic approach adopting PRISMA statement was implemented in this study. Three different databases (2010–2019) were screened and prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
129
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(147 citation statements)
references
References 72 publications
5
129
0
13
Order By: Relevance
“…Our results, however, are consistent with those of previous uncontrolled pilot intervention studies conducted on overweight and obese children of similar age and nationality [ 5 , 36 , 52 ], which revealed significant changes in PA and health-related fitness tests. Our findings are also in line with the results of previous studies showing the effectiveness of school-based interventions in promoting PA and physical fitness among obese children (for a review, see [ 28 ]). From this standpoint, the increased PA levels in the intervention group could be linked to the improvement in actual motor competence, as found in previous studies [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results, however, are consistent with those of previous uncontrolled pilot intervention studies conducted on overweight and obese children of similar age and nationality [ 5 , 36 , 52 ], which revealed significant changes in PA and health-related fitness tests. Our findings are also in line with the results of previous studies showing the effectiveness of school-based interventions in promoting PA and physical fitness among obese children (for a review, see [ 28 ]). From this standpoint, the increased PA levels in the intervention group could be linked to the improvement in actual motor competence, as found in previous studies [ 19 , 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…A recent systematic review suggests that school-based interventions can greatly contribute to prevent obesity and to promote PA and fitness if the programs are multicomponent; centered on PA; and focused on the content, quality, and duration [ 28 ]. Findings of a cross-sectional study on a large sample of students aged 6–18 years showed a physical activity-friendly school environment to be associated with lower risk of obesity [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The WHO has further stated that children and adolescents are the most important population for fostering the adoption of healthy lifestyles in the future [28]. In addition, as school-based health promotion programs exert positive effects on children's and adolescents' health [29,30], consideration should also be given to efforts to increase awareness about these issues among SHS members in the process of developing the training program.…”
Section: Discussionmentioning
confidence: 99%
“…Physical inactivity is widely recognized as a risk factor for illnesses in adulthood [1][2][3]. Health-promoting interventions, including enhanced physical activity and exercise programs showed promising results in different life stages [4]. An increase of physical activity is also associated to an increase in physical fitness [5], and such increased level of fitness has a positive effect on health [6].…”
Section: Introductionmentioning
confidence: 99%